Nordic education policy construction as a model for reforming Indonesia's national education system towards SDG-based digital transformation - Dhofarina Firda Kamala; Dinda Ayu Halimatus Sa’diyah; Nur Jihan (Green Governance: Exploring Politics, Social Justice, and the Environment, 2026)
Background: Digital transformation in education has become a strategic necessity in the era of Society 5.0, when technology serves not only as an industrial tool but also as a means of improving the quality of human life. This study analyzes the consistency of education policies in Scandinavian countries particularly Finland as a model for Indonesia in realizing sustainable and equitable digital education transformation. Methods: Using qualitative research methods with a literature review approach, this study examines policy documents, scientific literature, international reports, and national regulations to compare the direction of digital education policies in Finland and Indonesia. Findings: The results show that Finland's success is supported by long-term policy stability, research-based curriculum renewal, coordinated decentralization, teacher readiness as key actors, equitable digital infrastructure, and strict data protection. In contrast, Indonesia still faces challenges in the form of overly rapid curriculum changes, inconsistent policy direction, infrastructure gaps, and low digital competence among some educators. Conclusion: This study concludes that Indonesia can achieve an inclusive, adaptive, and sustainable digital education transformation through long-term policy consistency, multi-stakeholder collaboration, and the integration of local values as the foundation for national policy development. Novelty/Originality of this article: This study offers a policy reformulation model in the form of a Grand Design for Digital Education Transformation and the establishment of INDEC as a data-based national evaluation and coordination center.